ANALISIS KETIMPANGAN PEMBANGUNAN ANTARKABUPATEN/KOTA DI PROVINSI KALIMANTAN SELATAN TAHUN 2010-2017 - Maulana, Arif (Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
One of the problems that still cannot be resolved in Indonesia is the inter-regional inequality. Some regions experience fast economic growth but the other one get slow economic growth. One of the provinces that cannot be separated from this problem is South Kalimantan Province. The purpose of this study was to determine the extent of development inequality between districts/cities in South Kalimantan Province in 2010-2017. This study was conducted using a quantitative descriptive approach using Gross Regional Domestic Product (GRDP) and population data. The analytical tool used is the Williamson Index Analysis and Klassen Typology. The results of the study show that inequality between districts/cities in the South Kalimantan Province is still worrying, showed through the Williamson Index shows the middle and high levels because it is around 0,5. An important finding that should be noticed in this study is districts that have a large dependence on coal mining are in quadrant 2 (high income but low growth) and quadrant 4 (low growth and low income) based on the results of the Klassen Typology.